Answer:
-19 = x
Step-by-step explanation:
Step 1: Write equation
-4(x + 1) - 3 = -3(x - 4)
Step 2: Solve for <em>x</em>
<u>Distribute:</u> -4x - 4 - 3 = -3x + 12
<u>Combine like terms:</u> -4x - 7 = -3x + 12
<u>Add 4x on both sides:</u> -7 = x + 12
<u>Subtract 12 on both sides:</u> -19 = x
9514 1404 393
Answer:
15. f(x) +g(x) = 7x +2
16. f(x) -g(x) = -3x +8
17. h(x) · g(x) = 35x -21
Step-by-step explanation:
Substitute the function definition for each function expression and simplify.
__
15. f(x) + g(x) = (2x +5) +(5x -3)
f(x) +g(x) = 7x +2
__
16. f(x) - g(x) = (2x +5) -(5x -3)
f(x) -g(x) = -3x +8
__
17. h(x) · g(x) = (7) · (5x -3)
h(x) · g(x) = 35x -21
Answer:
112
Step-by-step explanation:
I am not 100% sure because I can't see information given on the shape, but assuming it is equal angles
Answer:
90° clockwise rotation rule (about the origin) for a point
Step-by-step explanation:
(x , y) → (y, -x)
Swap x and y......change the sign on x
Can you take it from here ???
1/2 is one half---Erin
6/8=3/4----Laurn
Lauran scored mor goals because she scored 3/4 which is more than 1/2